The Effectiveness of Zeolite-Activated Charcoal in Reducing Iron and Manganese Levels in Well Water of Milala Housing in Pancur Batu District, North Sumatra - Haesti Sembiring (Jurnal Multidisiplin Madani, 2023)
Dug wells are a means of providing clean water that belongs to shallow groundwater and generally contains high levels of iron (Fe) and manganese (Mn). The presence of high levels of iron in water is marked by yellow-brown water color and unpleasant odor. Excess iron can cause poisoning, intestinal damage, premature aging to sudden death, impaired absorption of vitamins and minerals, and hemochromatosis. Based on the observation of the researchers on the condition of the dug well water of the community in Milala Rumah Tengah Block E Simpang Gardu Subdistrict Pancur Batu, it can be seen that the dug well water is very yellow and the community uses it as a source of clean water. The results showed that the iron content of the dug well water in two houses before treatment was >4 mg/l and the manganese content in the first house was 2.60 mg/l and in the second house was 3.02 mg/l. After treatment using activated charcoal zeolite for ten days, the average iron content decreased to 0.08 mg/l (98%) and the average manganese content decreased to 0.26 mg/l (90%)